Optimization of the cooling system design for a compact high-power LED luminaire - Pekur, D.V.; Nikolaenko, Yu.E.; Sorokin, V.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2020)
Using the method of computer modelling, considered in this paper, is the optimization of a passive air system design for cooling the powerful LED luminaire based on heat pipes and cooling rings. Thermal and mass characteristics of the cooling system have been studied for various design parameters: distance between rings, thickness of ring materials, and thermal loads. It has been shown that, to provide a minimal case temperature of the LED source, the optimal distance between cooling rings should be 6 mm, but in this case, the mass of the cooling system is not least. To reduce the luminaire mass, it is reasonable to choose the distance between the cooling rings equal to 8 mm. Then the temperature of the light source increases by only 1.8 °С, or by 2.2%, while the mass of the cooling system reduces by 1357 g, or by 20.5%. At the same time, lowering the ring thickness from 2 to 0.8 mm can, in addition, reduce this mass by 2700 g, or by 48.6%. However, when doing so, the temperature of LED source case is increased by 5.9 °С. The offered cooling system based on heat pipes is capable of providing the thermal resistance 0.131 °С/W when scattering the thermal power 500 W under the maximum temperature of the LED source crystal 135.5 °С. Recommendations for the application of the developed cooling system have been formulated.